Condições de qualidade na oferta educacional para estudantes com deficiência intelectual no Espírito Santo - Bazilatto, Alexandre (2023)
We aim to generate analyzes on the quality conditions in the educational offer for students with intellectual disabilities enrolled in public schools of common education linked to the state education system of Espírito Santo, seeking to: a) Develop reflections on the quality conditions in the educational offer for students with intellectual disability; b) Develop understandings about how teachers, in their work spaces, experience and perceive quality conditions in the educational provision for students with intellectual disabilities. This is figurational research (ELIAS; SCOTSON, 2000) that uses conversation circles as the main methodological procedure (MATURANA, 1997). The conversation circles took place in synchronous (online) meetings of the extension course “Special Education: the production of pedagogical practices in the common education school”, offered by the Center for Teaching, Research and Extension in Special Education (Neesp), Centro of Education (CE) of the Federal University of Espírito Santo, from June to August 2021, under registration 2448/2021 (Dean of Extension – PROEX). The subjects of this research were 08 (eight) regular education teachers and 02 (two) teachers specializing in special education in the area of intellectual disabilities. The analyzes were based on the constructs of Figurational Sociology, developed by Norbert Elias, particularly the concepts of “common fund of experiences” and “social fund of knowledge” (ELIAS, 1994b), in dialogue with the literature that deals with quality of teaching and on educational provision for students with intellectual disabilities. From the data, we observed that teachers experience and realize that the quality conditions in the educational provision for students with intellectual disabilities are closely related to collaborative work, therefore, this process needs to be guided by the need to overcome the idea of socialization influenced by prejudices and the search for normalization, opting for an education that values the autonomy and educational potential of students with intellectual disabilities; We highlight that teachers express the need to value public schools, emphasizing improvements in infrastructure, pedagogical methods and consistent salaries to guarantee quality conditions for students with intellectual disabilities. This supports our understanding that quality, just like language and knowledge, “[...] can operate as a prototype model of a social factor” (ELIAS, 1994b, 22), in which its representation is modelable to based on the stimuli and the evident interrelationship of individuals.